DUKUNGAN SOSIAL KELUARGA DENGAN TINGKAT STRES ANGGOTA KELUARGA YANG MERAWAT PASIEN GANGGUAN JIWA - Herawati; Wulandari, Yolla Yollanda; Setyowati, Anggi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2016)
Family social support is a very important coping strategy of a family by the time ofexperiencingstress. Stress refers to any situation when non specific demand requires an individual to respondor to act. Objective to know the correlation between family social support and stress degree offamily member in treating mental disorder patient in the work region of Banjarbaru Puskesmas.Methods this is an observation analytic study using cross sectional design and the data iscollected by means of giving questionnaires on family social support and stress degree. Resultsthe study indicates that most of the respondents, namely 25 respondents (78.13%) have goodfamily social support, and 6 respondents (18.75%) have sufficient family support and only 1respondents (3.13%) has less family social support. The respondents stress degree shows thatgenerally, namely 18 respondents (56.25%) have stress degree a little bit lower than the average.The data analysis of the study has applied spearman correlation test with p value 0.041 <0.05,there is a negative correlation with the low power between the family social support and thestress degree of family member in treating patient with mental disorder in the work region ofBanjarbaru Puskesmas with r value = -0,363.